Analisis Rasio Keuangan sebagai Dasar Penilaian Kinerja Keuangan Sebelum dan Setelah Munculnya Pandemi Virus Corona (Covid-19) di Rumah Sakit UNS - Nur Sidiq, Anas Harya; Luhgiatno, Luhgiatno; Wahyuningsih, Panca (STIE PENA, 2022)
This study aims to analyze financial ratio analysis as the basic for assessment of financial performance before and after the event of the corona virus pandemic (covid-19) in uns hospital. This type of research is a retrospective study with descriptive and analytical research methods. Retrospective research is research that seeks to look back (backward looking) where research explains past data. Descriptive research method is a research method that is carried out with the main aim of making a picture or description of a situation objectively. This study describes the calculation of financial ratios using the analysis of liquidity ratios, solvency ratios, activity ratios and profitability ratios at UNS Hospital for the 2018-2020 period. The financial reporting period in 2018 was chosen because this year the conditions at the UNS Hospital have not been affected by the Corona virus pandemic. The financial report for 2020 was chosen because this year UNS Hospital has been affected by the Corona virus. The purpose of this study is that readers can find out financial performance based on the results of analysis of liquidity ratios, solvency ratios, activity ratios, and profitability ratios at UNS Hospital before and after the emergence of the Corona virus in Indonesia and find out the comparison of the results of the analysis of liquidity ratios, solvency ratios, activity ratios, and profitability ratios before and after the emergence of the Corona virus in Indonesia.Keywords: liquidity ratio, solvency ratio, activity ratio, and profitability ratio